Facilitators and barriers for implementation of a novel resuscitation quality improvement package in public referral hospitals of Nepal - Niina Ekström; Rejina Gurung; Urja Humagain; Omkar Basnet; Pratiksha Bhattarai; Nishant Thakur; Riju Dhakal; Ashish KC; Anna Axelin (BMC, 2023)
Abstract Background Improving the healthcare providers (HCP) basic resuscitation skills can reduce intrapartum related mortality in low- and middle-income countries. However, the resuscitation intervention's successful implementation is largely dependent on proper facilitation and context. This study aims to identify the facilitators and barriers for the implementation of a novel resuscitation package as part of the quality improvement project in Nepal. Methods The study used a qualitative descriptive design. The study sites included four purposively chosen public hospitals in Nepal, where the resuscitation package (Helping Babies Breathe [HBB] training, resuscitation equipment and NeoBeat) had been implemented as part of the quality improvement project. Twenty members of the HCP, who were trained and exposed to the package, were selected through convenience sampling to participate in the study interviews. Data were collected through semi-structured interviews conducted via telephone and video calls. Twenty interview data were analyzed with a deductive qualitative content analysis based on the core components of the i-PARiHS framework. Results The findings suggest that there was a move to more systematic resuscitation practices among the staff after the quality improvement project's implementation. This positive change was supported by a neonatal heart rate monitor (NeoBeat), which guided resuscitation and made it easier. In addition, seeing the positive outcomes of successful resuscitation motivated the HCPs to keep practicing and developing their resuscitation skills. Facilitation by the project staff enabled the change. At the same time, facilitators provided extra support to maintain the equipment, which can be a challenge in terms of sustainability, after the project. Furthermore, a lack of additional resources, an unclear leadership role, and a lack of coordination between nurses and medical doctors were barriers to the implementation of the resuscitation package. Conclusion The introduction of the resuscitation package, as well as the continuous capacity building of local multidisciplinary healthcare staff, is important to continue the accelerated efforts of improving newborn care. To secure sustainable change, facilitation during implementation should focus on exploring local resources to implement the resuscitation package sustainably. Trial Registration Not applicable.